Marijuana Legalization and U.S. Postal Inspection Service Seizures: An Exploration of Black Market Activity - Worrall, John L. (American journal of criminal justice, 2022)
Researchers have explored the effects of marijuana legalization on a range of outcomes, including crime and public health. Relatively few, however, have explored the effects of legalization on measures of black market activity. To fill a gap in the literature, this study examined the effects of recreational and medical marijuana legalization on United States Postal Inspection Service (USPIS) marijuana seizure activity. A state-level panel data analysis (with data from 2010 - 2019) revealed that states’ legalization schemes were correlated with seizures. Specifically, medical legalization was associated with increased seizures, irrespective of shipment origin. The key takeaway is that legalization affects black market activity, as measured by federal USPIS seizures. This is important because prior studies of the marijuana legalization—black market nexus were either speculative as to the connections or concerned solely with drug pricing. Implications and limitations are discussed.